2018
DOI: 10.1088/1755-1315/102/1/012084
|View full text |Cite
|
Sign up to set email alerts
|

Physical, chemical and sensory properties of brownies substituted with sweet potato flour (Ipomoea batatasL.) with addition of black cumin oil (Nigella sativaL.)

Abstract: Abstract. Effect of addition black cumin oil on the physical (hardness) characteristics, chemical (water, ash, fat, protein, carbohydrate, antioxidant IC50, total phenol and active component) characteristics and sensory (flavor, taste, texture, overall) characteristics of brownies substituted sweet potato flour were investigated. Substituted brownies was added with 0.05%, 0.10%, 0.15%, 0.20% and 0.25% of nigella sativa oil. The result showed that water content, ash, protein, fat, total phenol were increased an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…Another similar study was conducted on the sensory evaluation of Nigella sativa supplemented breads and found that substitution of 5% of flour in bread with Nigella sativa depicted satisfactory consumer acceptability in terms of flavor, texture, aroma and overall acceptability [21]. Ligarnasari et al (2018) reported that addition of Nigella sativa oil in brownies improved their sensory attributes [22]. Melapa (2015) have reported that soft texture of the product is influenced by its water content, fat as well as protein content and the use of baking ingredient [23].…”
Section: Sensory Analysis Of Breadsmentioning
confidence: 96%
“…Another similar study was conducted on the sensory evaluation of Nigella sativa supplemented breads and found that substitution of 5% of flour in bread with Nigella sativa depicted satisfactory consumer acceptability in terms of flavor, texture, aroma and overall acceptability [21]. Ligarnasari et al (2018) reported that addition of Nigella sativa oil in brownies improved their sensory attributes [22]. Melapa (2015) have reported that soft texture of the product is influenced by its water content, fat as well as protein content and the use of baking ingredient [23].…”
Section: Sensory Analysis Of Breadsmentioning
confidence: 96%
“…However, comparing these results to other pastry products made from banana flour blends, a contrasting result was found with the study of [24]. They described the characteristics of biscuits made using hot air-dried banana flour and freeze-dried banana flour.…”
Section: Effects Of Bpsf On the Acceptability Of Brownies Formulations Based On Sensory Attributesmentioning
confidence: 69%
“…Processing banana pseudostem into flour can improve their shelf life [20], and the use of such as a partial replacement for wheat flour can increase dietary fiber consumption. It also improves the nutritional value of white bread and some essential macro and micro minerals [21], and other pastry products like brownies, described as food with less balanced nutrients and a lower food value that the body can use [24]. Hence incorporating BPSF in its production improves its nutritional value.…”
Section: Introductionmentioning
confidence: 99%
“…Umumnya, brownies disajikan dalam bentuk slice dan dikonsumsi sebagai makanan selingan bersama dengan teh atau kopi. Bahan dasar produk brownies yaitu tepung terigu protein rendah, telur, lemak, gula pasir, dan coklat (Ligarnasari et al, 2018).…”
Section: Pendahuluanunclassified